2017
DOI: 10.1590/s1984-29612017024
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites in stray and shelter cats in the municipality of Rio de Janeiro, Brazil

Abstract: The increasingly urban nature of the population has led many people to choose independent pets, such as cats. This situation has also made it possible for these animals to be abandoned, thus increasing the numbers of cats on the streets and in shelters. These animals can act as a source of infection for other hosts. Between 2014 and 2015, the frequency of gastrointestinal parasites in captive and stray cats in the municipality of Rio de Janeiro was analyzed. Ninety-one fecal samples were collected from captive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
(42 reference statements)
4
10
0
3
Order By: Relevance
“…Likewise, many cat owners believe that indoor cats are not exposed to parasites and therefore do not take the appropriate preventive measures (Diakou et al, 2017). Pereira et al (2017) found the prevalence of endoparasite infection among shelter cats in the city of Rio de Janeiro to be 49.5%, comparable to the 50.64% found in the present study. Serra et al (2003) studied stray cats in the metropolitan area of Rio de Janeiro and reported a 63.4% prevalence of endoparasite infection.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Likewise, many cat owners believe that indoor cats are not exposed to parasites and therefore do not take the appropriate preventive measures (Diakou et al, 2017). Pereira et al (2017) found the prevalence of endoparasite infection among shelter cats in the city of Rio de Janeiro to be 49.5%, comparable to the 50.64% found in the present study. Serra et al (2003) studied stray cats in the metropolitan area of Rio de Janeiro and reported a 63.4% prevalence of endoparasite infection.…”
Section: Discussionsupporting
confidence: 78%
“…Gennari et al (2016) analyzed stool samples from cats in the metropolitan region of São Paulo and found a 0.4% prevalence of dipylidiasis. Pereira et al (2017) found the prevalence of dipylidiasis to be 2.2% and 6.7% among stray and shelter cats, respectively, in the city of Rio de Janeiro. Monteiro et al (2016) identified dipylidiasis in 0.88% of stool samples collected from household cats in the northeastern region of the country.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations